1963
DOI: 10.1136/bmj.2.5368.1311
|View full text |Cite
|
Sign up to set email alerts
|

Nalidixic Acid in Urinary Infections

Abstract: Nalidixic acid (" negram ") is one of a new series of 1,8-naphthyridine derivatives with antibacterial properties which have been synthesized by Lesher et al. (1962). Chemically it is 1-ethyl-7-methyl-1,8-naphthyridine-4-one-3-carboxylic mg./kg. throughout pregnancy and for one week afterwards. On these dose levels there were no adverse effects on the course of pregnancy or on the growth and survival capacities of the offspring. At the highest dose level of 300 mg./kg., which is that approaching the limit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
2

Year Published

1965
1965
1982
1982

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…It is well known from early work on the compound [5][6][7] that the activity of nalidix-ic acid in vitro is affected by the density of the bacterial inoculum and by the ready emergence of bacterial resistance, and clini cal trials [5,[7][8][9][10][11][12][13][14] have confirmed that re sistance can also emerge during nalidixic acid therapy. However, the frequency with which such resistance is encountered in clin ical practice has been the subject of con troversy [15] and little is known of the con ditions which favour or oppose the emer gence of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known from early work on the compound [5][6][7] that the activity of nalidix-ic acid in vitro is affected by the density of the bacterial inoculum and by the ready emergence of bacterial resistance, and clini cal trials [5,[7][8][9][10][11][12][13][14] have confirmed that re sistance can also emerge during nalidixic acid therapy. However, the frequency with which such resistance is encountered in clin ical practice has been the subject of con troversy [15] and little is known of the con ditions which favour or oppose the emer gence of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…High urinary levels were obtained in human volunteers following moderate oral dosage. There was little ill-effect and the drug was used successfully in a series of clinical trials (Lishman and Swinney, 1963;Barlow, 1963;Ward-McQuaid, Jichlinski, and Macis, 1963). It has come to be regarded as an effective antibacterial agent for urinary infections.…”
mentioning
confidence: 99%
“…Nalidixic acid (Negram) has been used to treat urinary-tract infections (Lishman and Swinney, 1963;Barlow, 1963;Jameson and Swinney, 1963;Ward-McQuaid et al, 1963;Swinney, 1964). The results obtained were encouraging and led to the study of the tissue concentration of nalidix acid in the pyelonephritie kidney.…”
mentioning
confidence: 99%